Фомка - белый медвежонок: [рассказы] / Вера Чаплина - Чаплина Вера Васильевна (Библиотека школьника, 2005)
Экземпляры: ф. 2 (20130307) / Инвентарный номер: 99494 / Цена: 70 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ч-19 / ББК: 84(2Рос=Рус)6